2003
DOI: 10.1111/j.1460-9568.2003.03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizures preferentially stimulate proliferation of radial glia‐like astrocytes in the adult dentate gyrus: functional and immunocytochemical analysis

Abstract: Kainate-induced seizures increase hippocampal neurogenesis. Glial fibrillary acidic protein-positive astrocytes with radial processes in the dentate gyrus share many of the characteristics of radial glia and appear to act as precursor cells for adult dentate neurogenesis. Using the chemoconvulsant kainate and transgenic mice with human glial-fibrillary acidic protein (hGFAP) promoter-controlled enhanced green fluorescent protein (EGFP) expression, we examined the proliferation, morphology and electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
130
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 49 publications
(78 reference statements)
11
130
0
1
Order By: Relevance
“…Additionally, a recent report from Varodayan et al [48] demonstrated that seizure leads to a shortening of the cell cycle in DG precursors, suggesting a link between G 1 phase length and seizureinduced proliferation. To address whether Cdk6 plays a role during seizure-induced proliferation, we injected kainic acid (KA) to WT and Cdk6 À/À animals and quantified precursor cell proliferation in the DG 72 hours later, with a protocol that was described previously [49,50]. Of note, we consistently observed a large overlap between Cdk4/6 and Ki-67 expression 72 hours after either NaCl or KA administration (Supporting Information Fig.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, a recent report from Varodayan et al [48] demonstrated that seizure leads to a shortening of the cell cycle in DG precursors, suggesting a link between G 1 phase length and seizureinduced proliferation. To address whether Cdk6 plays a role during seizure-induced proliferation, we injected kainic acid (KA) to WT and Cdk6 À/À animals and quantified precursor cell proliferation in the DG 72 hours later, with a protocol that was described previously [49,50]. Of note, we consistently observed a large overlap between Cdk4/6 and Ki-67 expression 72 hours after either NaCl or KA administration (Supporting Information Fig.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 87%
“…7A-7E). Because seizure has been demonstrated to initially trigger the proliferation of immature/noncommitted precursors [49,50], we then quantified the numbers of GFAP þ /Ki-67 þ and Sox2 þ /Ki-67 þ cells following KA injection. We observed a dramatic increase of the number of GFAP þ and Sox2 þ proliferating precursors, independently of the mouse genotype (Fig.…”
Section: Seizure-induced Proliferation and Neurogenesis In Cdk6 2/2 Micementioning
confidence: 99%
“…How these proliferating RG-like cells are integrated into the hippocampal network is poorly understood. Epileptic seizures or ischemic insults can trigger proliferation of RG-like cells, while the transit-amplifying progenitors in the DG are less affected (3,5). However, RG-like precursor cells neither receive functional GABAergic nor glutamatergic synaptic input (6,7).…”
mentioning
confidence: 99%
“…In the subgranular zone (SGZ) of the dentate gyrus (DG), astrocytes with a radial glia (RG)-like morphology are considered stem cells (1). They extend a long branching process through the granule cell layer (GCL), electrophysiologically display a passive current pattern (2)(3)(4), and express GFAP and nestin. How these proliferating RG-like cells are integrated into the hippocampal network is poorly understood.…”
mentioning
confidence: 99%
“…In addition, these precursors may develop into non-neuronal cells. Indeed, their development may arise entirely from radial glia, dividing into one or more daughter cells that become neurons, as well as additional cells that ultimately become mature astrocytes [20,21].…”
Section: Npy and Dentate Gyrus Neurogenesismentioning
confidence: 99%